BANGLADESHI MUSLIM CONSTRUCTION WORKERS IN SINGAPORE: A STUDY IN THE PROCESS OF MIGRATION AND EMPLOYMENT - Sanghita Datta (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2015)
Singapore has a long history of receiving labor migrants from all across South Asia and it has systematically developed a whole range of strategies to deal with the shortage of labourers in the country. Recent research has shown that to fulfill these shortages, large numbers of labourers are hired from Bangladesh Muslim. These labourers are temporary migrants and work in various construction sites in the country. Using field research (unstructured interviews and purposive sampling) as the chief method, with supporting secondary data from library research newspaper archives and internet, this research focuses on Bangladesh's migrant workers in Singapore specifically working in the construction sites. It will look at what goes into the decision making or the choice of a certain foreign country over the other and the role of the family in the decision making process. Understanding the process of socialization among these migrants and how they try to bridge the gaps between their home and the foreign work place by creating a home away from home, will also be highlighted. Singapura memiliki sejarah panjang menerima tenaga kerja migran dari seluruh Asia Selatan dan telah sistematis mengembangkan berbagai macam strategi untuk menghadapi kekurangan buruh di negara ini. Penelitian terbaru menunjukkan bahwa untuk memenuhi kekurangan tersebut, sejumlah besar buruh dipekerjakan dari Bangladesh Muslim. Para buruh ini merupakan migran sementara dan mereka bekerja di berbagai konstruksi di negara ini. Dengan menggunakan penelitian lapangan (wawancara terstruktur dan purposive sampling) sebagai metode utama, dengan didukung oleh data sekunder dari perpustakaan, arsip, koran, penelitian, dan internet, penelitian ini berfokus pada pekerja migran Bangladesh di Singapura secara khusus bekerja di lokasi konstruksi. Penelitian ini akan melihat apa yang terjadi dalam pengambilan keputusan atau pilihan dari negara asing tertentu atas yang lain dan peran keluarga dalam proses pengambilan keputusan. Memahami proses sosialisasi di antara para migran dan bagaimana mereka mencoba untuk menjembatani kesenjangan antara keluarga dan tempat kerja asing dengan menciptakan suasana seperti dirumah sendiri meskipun mereka jauh dari rumah juga akan disorot.